contestada

PLEASE HELP ME

1. Find the product of -3x^3 + 2x – 4 and 3x – 2

2. Is the product of -3x^3 + 2x – 4 and 3x – 2 equal to the product of -3x^3 + 2x – 4 and 2x-3?

Respuesta :

Answer:

Step-by-ste ((2•(x4))-(3•(x3)))-2x2  = 0

STEP

2

:

Equation at the end of step

2

:

 ((2 • (x4)) -  3x3) -  2x2  = 0

STEP

3

:

Equation at the end of step

3

:

 (2x4 -  3x3) -  2x2  = 0

STEP

4

:

STEP

5

:

Pulling out like terms

5.1     Pull out like factors :

  2x4 - 3x3 - 2x2  =   x2 • (2x2 - 3x - 2) p explanation:

ACCESS MORE